Quantum Yield‐Engineered Biocompatible Probes Illuminate Lung Tumor Based on Viscosity Confinement‐Mediated Antiaggregation. (28th August 2019) - Zhang, Kun; Li, Hong‐Yan; Lang, Jin‐Yi; Li, Xiao‐Tong; Yue, Wen‐Wen; Yin, Yi‐Fei; Du, Dou; Fang, Yan; Wu, Hong; Zhao, Yong‐Xiang; Xu, Chuan
Abstract: Low quantum yield and aggregation‐mediated quenching are two concerns for fluorescence imaging. However, there are not yet general means available for addressing these issues. Herein, a viscosity confinement‐mediated antiaggregation strategy is established to enable the improved fluorescence properties of entrapped fluorophores in dye‐encapsulation nanotechnology including quantum yield, fluorescence lifetime, and photostability. To instantiate this strategy, solid DL‐menthol (DLM) is introduced to disperse entrapped indocyanine green (ICG) fluorophores when coencapsulating DLM and ICG molecules in organic poly(lactic‐co‐glycolic acid) carriers. Depending on the robust ability of highly viscous DLM to augment the migration barrier and diminish diffusion coefficient, ICG aggregation and aggregation‐mediated quenching are demonstrated to be theoretically and experimentally inhibited, resulting in prolonged fluorescence lifetime, increased quantum yield, and facilitated radiative process. Consequently, the fluorescence imaging ability and photostability are significantly improved, enabling the in vitro, cellular‐level, and in vivo fluorescence imaging. More significantly, this solid DLM‐mediated antiaggregation strategy can act as a general method to extend to the intermolecular fluorescence resonance energy transfer (FRET) process and improve FRET efficiency via inhibiting the aggregation‐mediated quenching. Abstract : Solid DL‐menthol is introduced into poly(lactic‐co‐glycolic acid) carriers to disperse entrapped fluorophores and establish a viscosity confinement‐mediated antiaggregation strategy for inhibiting quenching and improving fluorescence imaging properties associated with quantum yield, fluorescence lifetime, and photostability via the high viscosity‐mediated migration barrier elevation, which provides a new avenue to improving fluorescence imaging of entrapped fluorophores in dye‐encapsulation nanotechnology.